2001
DOI: 10.1053/rapm.2001.25935
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of QT interval and QT dispersion following stellate ganglion block using computerized measurements

Abstract: Right SGB induces increases of the QT interval, QTc interval, QTD, and QTcD, and left SGB induces decreases of the QT interval and QTc interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 25 publications
2
29
0
1
Order By: Relevance
“…Reported major complications from stellate blocks are rare but include intravascular injection with cardiac and neurotoxicity, intrathecal injection, and pneumothorax. Right stellate ganglion blocks have been shown to increase the QT interval 14 and may cause a slight reduction in cardiac output. 15 Performing any nerve block in an unconscious patient should not be taken lightly because of the lack of explicit consent and the importance of patient feedback in helping detect a poorly positioned needle.…”
Section: Discussionmentioning
confidence: 99%
“…Reported major complications from stellate blocks are rare but include intravascular injection with cardiac and neurotoxicity, intrathecal injection, and pneumothorax. Right stellate ganglion blocks have been shown to increase the QT interval 14 and may cause a slight reduction in cardiac output. 15 Performing any nerve block in an unconscious patient should not be taken lightly because of the lack of explicit consent and the importance of patient feedback in helping detect a poorly positioned needle.…”
Section: Discussionmentioning
confidence: 99%
“…Eine re le van te Be ein flussung der kar dia len sym pa thi schen In nerva ti on ist auch un ter In ters ka le nus-und Gan gli on-stel la tum-Blo cka de zu er warten. Da bei hat eine Blo cka de des Gan glion stel la tum auf der lin ken Sei te we ni ger Aus wir kun gen auf die QT c als auf der Gegen sei te [26].…”
Section: Lo Kal-und Re Gio Nal An äS the Sieunclassified
“…1 Left SGB induces a significant decrease of QT interval and QTc interval. 1 The postural change from supine to the head-up position also induces increases of QT interval and QTcD 3 and hemodynamic changes. 4 Increases of QT interval and QTD are associated with increased risks of arrhythmias and cardiovascular diseases.…”
mentioning
confidence: 96%
“…However, SGB and head-up tilt after the block may synergistically exert an unfavorable influence on electrocardiographic findings or hemodynamic parameters. [1][2][3][4] Our previous study showed that right SGB induces signifi-cant increases of QT interval, rate-corrected QT (QTc) interval, QT dispersion (QTD), and rate-corrected QT dispersion (QTcD). 1 Left SGB induces a significant decrease of QT interval and QTc interval.…”
mentioning
confidence: 99%
See 1 more Smart Citation